Benefits of 11C-methionine PET/MRI and intraoperative fluorescence in treating hyperparathyroidism. (29th July 2020) - Luong, Thien Vinh; Rejnmark, Lars; Arveschoug, Anne Kirstine; Iversen, Peter; Rolighed, Lars
Abstract : Multiple endocrine neoplasia 1 (MEN1) is a rare genetic syndrome characterized by the manifestation of tumors in endocrine glands most often in the parathyroid gland (PG). Treatment may involve several parathyroidectomies (PTX), especially in young patients, which increases the risk of postoperative complications. We present a 16-year-old patient with a family history of MEN1 syndrome. The patient started to show biochemical signs of hyperparathyroidism (HPT) and hypercalcemia at the age of 10. One and a half years later a PTX was successfully performed with removal of the two left PGs. However, a rise in plasma parathyroid hormone and ionized calcium was observed 4 years later. Preoperative noninvasive imaging with 99m Tc-sestamibi scintigraphy showed no definitive parathyroid adenoma. A 11 C-methionine position emission tomography combined with MRI (MET-PET/MRI) was then performed and detected a focus posterior to the lower part of the right thyroid lobe. Intraoperative angiography with fluorescence and indocyanine green dye was used to assess the vascularization of the remaining PGs. The lower right PG was removed. The patient was discharged with normalized biochemical values and without postoperative complications. Recurrence of primary HPT is frequent in MEN1 patients which often necessitates repeated operations. Our case report showed that the use of advanced noninvasive preoperative imaging techniques and intraoperative fluorescent imaging are valuable tools and should be taken into consideration in selected cases to avoid postoperative complications. To our knowledge, this is the first case where MET-PET/MRI has been used to detect parathyroid pathology. Learning points: MEN1 patients will develop parathyroid disease, which eventually will lead to surgical treatment with removal of the pathological glands. Preoperatively usage of MRI combined with PET tracers such as 11 C-methionine and 18 F-Fluorocholine are able to detect parathyroid pathology with a higher sensitivity than conventional imaging. Techniques using intraoperatively angiography with fluorescence and florescent dyes allow surgeons to verify the vascularization of each parathyroid gland. Optimization of noninvasive preoperative imaging techniques and intraoperative fluorescent imaging are valuable tools and should be taken into consideration when performing PTX consecutively in the same patient to avoid postoperative complications.